The Influence of Charismatic Leadership, Local Culture, Individual Characteristics on Work Ethic, Job Satisfaction and Performance of The Village Head On Lombok Island - Syahruddin; Lalu Moh. Kabul; Nizar Hamdi; Ahyat, Muhammad (Jurnal Ilmiah Sumber Daya Manusia, 2024)
The purpose of this research is to prove and analyze the influence of charismatic leadership, local culture, individual characteristics on work ethic, job satisfaction and performance of village heads on the island of Lombok.The sample in this study was village heads on Lombok Island, totaling 140 respondents who carried out proportional random sampling. The data analysis used in this study was the structural analysis model Equation Modeling (SEM) Version 19 using the AMOS 20.01 program. Structural equation model analysis Confirmatory Factor Analysis is to obtain path coefficient values ​​to prove the hypothesis. The results can be summarized as follows: Charismatic leadership has a significant effect on the work ethic, job satisfaction and performance of the village head, local culture has a significant effect on job satisfaction and performance but local culture has no significant effect on the work ethic of the village head, individual characteristics have a significant effect on the work ethic, job satisfaction and performance of the village head, work ethic has a significant effect on job satisfaction and performance of the village head and job satisfaction has a significant effect on the performance of the village head. The findings in this research carry empirical implications that individual characteristics, local culture, charismatic leadership, work ethic and job satisfaction can improve the performance of village heads on the island of Lombok.